Adaptive Thresholding in Chaos Engineering: Using Fuzzy Logic to Dynamically Set Alert Levels in Game Theoretical Frameworks - Manmohan, Nithin (Global journal of Business and Integral Security, 2024)
This research, titled "Adaptive Thresholding in Chaos Engineering: Using Fuzzy Logic to Dynamically Set Alert Levels in Game Theoretical Frameworks", explores a pioneering approach to enhancing system resilience and adaptability in chaotic environments. The study intergrates the principles of chaos engineering, fuzzy logic, and game theory to develop a comprehensive framework for dynamic threshold setting in complex systems.